Micro-extração em fase sólida (SPME) in situ e comparação de compostos voláteis em variedades de manga (Mangifera indica L.) resistentes e suscetíveis à mosca-das-frutas Anastrepha obliqua (Macquart) (Diptera: Tephritidae) - Tosta, Christiann Davis [UNESP] (2014)
Many commercial varieties of mango (Mangifera indica L.) are susceptible to pests called fruit flies, as Anastrepha obliqua, an important specie. This leads to the need of the use of chemical pesticides, burdening the production and generating environmental problems. Some mango varieties are resistant to fruit flies and therefore having factors that differentiate it when comparing to the susceptible. The objective of this study was to perform exploration of compounds and to identify factors of resistance and/or attraction. Peel characteristics were analyzed and volatile compounds obtained by solid phase micro extraction (SPME) in situ were identified and compared in the latex (sap) and fruits from resistant and susceptible varieties. This technique is useful to reveal the compounds really liberated on orchard, avoiding artefacts formation and the losing of compounds. Electroantenongraphic and wind tunnel attraction tests were performed using the proportion of the major compounds emitted by mango fruits. The results showed higher density of lactiferous ducts in the resistant variety and differences of latex and fruit volatile compounds profiles, as well as in different stages of ripening. Green fruits showed no esters, which became part of the main compounds in the total ripe stage, mainly ethyl octanoate and methyl octanoate. The α-copaene, α-gurjunene and β-selinene compounds seem possible role in repellency in unripe fruits, including possibly functioning as green stage markers, since their levels fall with maturation while its esters have increased. The compounds found in greater quantity in the condition of resistance were limonene, a- pinene, myrcene and humulene, while the condition of susceptibility were marked by ethyl octanoate, methyl octanoate, δ-3-carene and aloaromadendreno. The synthetic blend based on nine main compounds of the variety 'Palmer' proved attractive to Anastrepha...